Frequency of morbidity, mortality and renal trauma in blunt and firearm accidents in pediatric population. - Ahmed Quraishi, Mumtaz; Somroo, Kashifuddin Qayoom; Chand, Rewa; Rajpar, Zakir Hussain; Idrees Memon, Imran; Yousuf, Fakhir (International Journal of Endorsing Health Science Research, 2021)
Background: Renal Trauma is one of the significant causes of deterioration, morbidity, and mortality in the pediatric age group around the globe. Firearm injuries are among one of the essential causes for renal trauma. Overall, trauma is the leading cause of death and accounts for approximately 50% of mortality in children over 1 year of age. Therefore, the current study aims to determine the frequency of morbidity, mortality and renal trauma in blunt and firearm accidents in pediatric population. Methodology: A total of 180 children, aged up to 15 years with blunt and penetrating trauma, including firearm injuries, were enrolled in our study. All patients with in the inclusion criteria of the study, who were presented in the emergency department were evaluated and resuscitated by a pediatric surgeon. Patients indicated with renal trauma were operated and were post-operatively managed in the pediatric surgery ward. All patients included were followed as an outpatient. The data of this descriptive case series were collected prospectively and was analyzed on SPSS version 22.0. Results: Out of 180 patients 110 (61.11%) were male and 70 (38.89%) were female with mean age of 8.5 ± 2.9 years. Majority of the patients had blunt trauma (54.44%) followed by firearm injuries (60, 33.33%). While penetrating trauma were observed in 22 patients (12.22%). Overall Renal trauma was observed in 40 (22.2%) of patients. Out of 40 patients, 20 (50%) patients had blunt, while 14 (35%) had firearm and 05 (12.5%) had penetrating abdominal trauma. Majority of renal injuries were Grade II (60%) followed by Grade III (17.5%), Grade IV (12.5%) and Grade I (10%) injury. The major morbidities noted in firearm injured patients were surgical site infection that was reported in 33.33% patients, limb deformity in 6.66% and neurological deficit in 5% patients. Overall Mortality was observed in 6.6% patients and firearm injuries was responsible for 8.33%. Conclusion: Firearm injuries are one of the significant causes of trauma in children. The renal trauma was observed in 22.2% of cases, and all were managed conservatively. The frequency of morbidity and mortality secondary to firearm injuries was high as compared to other studies.